Pygoscelis antarctica - Hospitaleche, Carolina Acosta; Soto-Acuña, Sergio (Zenodo, 2023)
P. antarctica (MLP-O-14670, MLP-O-14671, MLP-O-14672, MLP-O-14673, MLP-O-14674, MLP-O-14675, MLP-O-14676, MLP-O-14677, MLP-O-14678, MLP-O-14679, MLP-O-14703, MLP-O-14704, MLP-O-14705, MLP-O-14706, MLP-O-14707, MLP-O-14708, MLP-O-14709, MLP-O-14710, MLP-O-14717, MLP-O-14737, MLP-O-14831, MLP-O-14905, MLP-O-14916, MLP-O-14947, MLP-O-15189, MLP-O-15190, MLP-O- 15191, MLP-O-15211, MLP 470). Published as part of Hospitaleche, Carolina Acosta & Soto-Acuña, Sergio, 2023, A small penguin cranium (Aves, Spheniscidae) from the Late Miocene of Bahía Inglesa Formation, Atacama Desert, Northern Chile, pp. 233-244 in Comptes Rendus Palevol 22 (13) on page 237, DOI:10.5852/cr-palevol2023v22a13, http://zenodo.org/record/14233130